Ultrastructural Study on Tissue Alterations Caused by Trypanosomatids in Experimental Murine Infections - Finol, Héctor J.; Roschman-González, Antonio (Frontiers in Public Health, 2014)
The ultrastructural study in different tissues of mice experimentally infected with isolates of Trypanosoma evansi, Trypanosoma cruzi and Leishmania mexicana reveals changes in cardiac myocytes, skeletal muscle fibers and hepatic, adrenal, kidney and spleen cells. Some were cytoarchitectural changes and other consisted of necrosis. Alterations were also found in microvasculature.The mononuclear cell infiltrate included neutrophils, eosinophils and macrophages. This work shows that various mice tissues are important target for trypanosomatids.